Limitations of population suppression for protecting crops from bird depredation: A review - Linz, George M. (2015)
Blackbirds (Icterinae) in North America, and dickcissels (Spiza americana Gmelin), eared doves (Zenaida auriculata Des Murs), and monk parakeets (Myiopsitta monachus Boddaert) in South America can cause serious economic damage to grain crops. Farmers frequently advocate lethal bird damage abatement measures based on the perceived need to take immediate action to avoid serious economic losses. In comparison, wildlife managers must make informed decisions based on a multitude of factors, including local, state, and national environmental laws, administrative restrictions, logistics, costs, expected outcome, and cultural considerations related to wildlife stewardship. In this paper, we focus on practicality, environmental safety, cost-effectiveness and wildlife stewardship to evaluate efforts to manage avian crop damage using lethal control. In each case where a lethal program was initiated, at least one of these four tenets was violated and there was temporary relief at best.